Endoscopic tissue sampling – Part 1: Upper gastrointestinal and hepatopancreatobiliary tracts. European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Pouw, Roos E.; Barret, Maximilien; Biermann, Katharina; Bisschops, Raf; Czakó, László; Gecse, Krisztina B.; de Hertogh, Gert; Hucl, Tomas; Iacucci, Marietta; Jansen, Marnix; Rutter, Matthew; Savarino, Edoardo; Spaander, Manon C. W.; Schmidt, Peter T.; Vieth, Michael; Dinis-Ribeiro, Mário; van Hooft, Jeanin E. (Endoscopy, 2021)
1 ESGE recommends that, where there is a suspicion of eosinophilic esophagitis, at least six biopsies should be taken, two to four biopsies from the distal esophagus and two to four biopsies from the proximal esophagus, targeting areas with endoscopic mucosal abnormalities. Distal and proximal biopsies should be placed in separate containers.Strong recommendation, low quality of evidence.2 ESGE recommends obtaining six biopsies, including from the base and edge of the esophageal ulcers, for histologic analysis in patients with suspected viral esophagitis.Strong recommendation, low quality of evidence.3 ESGE recommends at least six biopsies are taken in cases of suspected advanced esophageal cancer and suspected advanced gastric cancer.Strong recommendation, moderate quality of evidence.4 ESGE recommends taking only one to two targeted biopsies for lesions in the esophagus or stomach that are potentially amenable to endoscopic resection (Paris classification 0-I, 0-II) in order to confirm the diagnosis and not compromise subsequent endoscopic resection.Strong recommendation, low quality of evidence.5 ESGE recommends obtaining two biopsies from the antrum and two from the corpus in patients with suspected Helicobacter pylori infection and for gastritis staging.Strong recommendation, low quality of evidence.6 ESGE recommends biopsies from or, if endoscopically resectable, resection of gastric adenomas.Strong recommendation, moderate quality of evidence.7 ESGE recommends fine-needle aspiration (FNA) and fine-needle biopsy (FNB) needles equally for sampling of solid pancreatic masses.Strong recommendation, high quality evidence.8 ESGE suggests performing peroral cholangioscopy (POC) and/or endoscopic ultrasound (EUS)-guided tissue acquisition in indeterminate biliary strictures. For proximal and intrinsic strictures, POC is preferred. For distal and extrinsic strictures, EUS-guided sampling is preferred, with POC where this is not diagnostic.Weak recommendation, low quality evidence.9 ESGE suggests obtaining possible non-neoplastic biopsies before sampling suspected malignant lesions to prevent intraluminal spread of malignant disease.Weak recommendation, low quality of evidence.10 ESGE suggests dividing EUS-FNA material into smears (two per pass) and liquid-based cytology (LBC), or the whole of the EUS-FNA material can be processed as LBC, depending on local experience.Weak recommendation, low quality evidence.